Analisis Tingkat dan Upaya Pemeliharaan Kerusakan Jalan Soenandar Priyo Sudarmo, Kabupaten Sidoarjo - Anggi Dwi Anggraeny; Ibnu Sholichin; Aulia Dewi Fatikasari (Racic : Rab Construction Research, 2026)
Soenandar Priyo Sudarmo Road has a relatively high traffic intensity, especially heavy vehicles that support industrial activities in the Prambon area. This causes the road to often experience significant pressure and leading to various types of damage. Road damage needs to be taken seriously, as it directly impacts road service levels. Based on this This research aims to evaluate the extent of damage and the corresponding maintenance strategies for Soenandar Priyo Sudarmo Road. Primary data used includes road damage data and riding quality data, while secondary data includes geometric road data. This study employs the Indrasurya and Dirgolaksono (1990) method to analyze the severity of road damage and identify suitable maintenance strategies. The analysis results indicate that most road segments fall into the moderately critical damage category, with a Road Damage Value ranging from 40 to 90. The Riding Quality (RQ) assessment showed that most road sections were in the RQ3 (fair) category, meaning that standard speeds could still be achieved despite vibrations and more than two rough spots. Based on the obtained road damage values, most road segments are recommended for moderate maintenance, such as manual patching, sealing, and skin patching. Meanwhile, segments with minor damage are recommended for light maintenance, such as pothole repair, crack sealing, and leveling.